The Strategy Process / Concepts, Contexts, Cases: Second Edition - Mintzberg Henry; Quin Brian James (Prentice Hall International, 1991)
Acknowledgements, Introduction, Strategy, The Strategy Concept, The Strategist, Formulating Strategy, Strategy Analysis, Strategy Formation, Cases, Organization, Dealing with Structure and Systems, Dealing with Culture, Dealing with Power, Cases, Context, The Entrepreneurial Context, The Mature Context, The Diversified Context, The Professional Context, The Innovation Context, Managing Change, Thinking Strategically, Cases, Bibliography, Name and Subject Index.
Acknowledgements, Introduction, Strategy, The Strategy Concept, The Strategist, Formulating Strategy, Strategy Analysis, Strategy Formation, Cases, Organization, Dealing with Structure and Systems, Dealing with Culture, Dealing with Power, Cases, Context, The Entrepreneurial Context, The Mature Context, The Diversified Context, The Professional Context, The Innovation Context, Managing Change, Thinking Strategically, Cases, Bibliography, Name and Subject Index.